THE INFLUENCE OF INDEPENDENT ASSIGNMENTS ON STUDENTS’ INDIVIDUAL UNDERSTANDING IN THE INTRODUCTION TO INFORMATION TECHNOLOGY - Kurniawan, David Thanlian; Rondonuwu, Yeremia Victor (Jurnal Profesi Keguruan, 2024)
In the rapidly evolving era of information technology, students’ comprehension of the Introduction to Information Technology course at Pignatelli Triputra University is becoming increasingly vital. This course, which lays the foundation for understanding technologies such as computers, informatics, information systems, and electronics, demands up-to-date digital resources. However, observations indicate that students often struggle with complex topics such as scheduling in operating systems, the relational model in databases, and computer architecture. For instance, the topic of scheduling involves grasping algorithms like Round Robin and First Come, First Serve. To address these challenges, a self-directed learning initiative was implemented, incorporating independent assignments that yielded satisfactory results. Nevertheless, difficulties persist in the Final Semester Examination due to a lack of consistent practice and engagement with the semester’s course material. This study aims to develop tailored approaches to optimize students’ understanding of Introduction to Information Technology. A strategic improvement is required to enhance the effectiveness of self-directed learning, making it more suitable for students.